Desenvolvimento de um conversor Half-Bridge ressonante LLC para o acionamento de LEDs UV-C e aplicação em ação germicida - Costa, Marcelo Santos da (2023)
This master’s dissertation presents the development of a disinfection system based on UVC (ultraviolet type C), light-emitting diodes (LEDs). The motivation behind this work is to conceive a disinfection system using ultraviolet radiation for objects and surfaces in order to eliminate various fungi, bacteria, and viruses. LEDs are used due to their wavelength, particularly within the range of higher genotoxic potential, from 260 to 280 nm, as well as their construction characteristics, long lifespan, low power consumption, and small size. To measure the intensity and verify its efficiency, a monitoring system using sensors was employed to ensure that the system truly delivers the necessary magnitudes for germicidal action to eliminate different pathogens. The UV-C LEDs were driven by a resonant LLC half-bridge converter with an output power of 40 W. Zero Voltage Switching (ZVS), of the switches was sought at different frequency ranges. To control the current of the LED array, a proportional-integral (PI) controller was designed. The converter dynamic modeling was based on the extended descriptive function methodology, taking into account the piecewise linear (PWL) model of the LED. Additionally, the converter design and its entire control system were implemented. Biological tests were conducted on various types of bacteria with different measurements to verify the effectiveness of the LED germicidal action.